Understanding the Process and Nature of Grief and Loss in the Family Members of COVID-19 Victims: Developing and Elaborating the Model for Psychological Adjustment with Grief from a Mixed Methods Approach - Mansoori, Jamileh; Khodabakhshi-Koolaee, Anahita; Falsafinejad, Mohammad Reza; Kashani Vahid, Leila (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to examine the process and nature of grief and loss among family members of COVID-19 victims and to develop a model for psychological adjustment to grief in Tehran. Methods and Materials: This study utilized an exploratory sequential mixed methods design. The study population comprised survivors of COVID-19 victims in Tehran who had lost loved ones during the COVID-19 pandemic in 2021. In the qualitative phase, 20 survivors were selected through purposive sampling and participated in semi-structured interviews. The interview data were analyzed using conventional qualitative content analysis, leading to the development of a psychological adjustment to grief model based on the findings. In the quasi-experimental phase, 32 survivors from Mostafa Khomeini Hospital were selected via simple random sampling and randomly assigned to intervention and control groups, each with 16 participants. Data were collected using the Grief Experience Questionnaire (GEQ; Barrett & Scott). The intervention group participated in 14 sessions, each lasting 1.5 hours, employing the psychological adjustment to grief model. Data were analyzed using multivariate analysis of covariance (ANCOVA) with SPSS software (version 26). Findings: The qualitative phase revealed three selective codes: “contextual factors affecting grief,” “the nature and process of grief,” and “coping with and managing grief.” Quantitative phase results demonstrated a significant difference between pre-test and post-test scores in the intervention group. ANCOVA results indicated the developed psychological adjustment model significantly affected the bereaved survivors of COVID-19 victims (η² = 0.962; p < 0.0001; F = 739.978). Conclusion: The psychological adjustment model, developed based on the context and experiences of bereaved survivors of COVID-19 victims in Tehran, improved psychological adjustment to grief. Counselors can employ this intervention to assist survivors in adjusting to grief, thereby enhancing their level of adjustment.